The Influence of Teaching Methods and Learning Media on Learning Outcomes Students: a Quasi-Experimental Study - Asbupel, Fatnan; Angela, Lia; Alfian, Muhammad (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
This study aims to determine the effect of teaching methods and learning media on student learning outcomes in chemistry subjects, as well as the interaction between the two. This study is a quasi-experiment with a 2x2 factorial Completely Randomized Design (CRD) design, which considers moderator variables that may affect the relationship between independent and dependent variables. The study population was grading the instrument used was a multiple-choice objective test whose validity was tested logically and empirically. The homogeneity test used the Levene Test and the hypothesis was tested using Two-Way Analysis of Variance (Two Way ANOVA). The results showed that: (1) the PBL teaching method provided higher chemistry learning outcomes than the conventional method (p = 0.023 < α = 0.05); (2) the use of audiovisual media produced higher learning outcomes than visual media (p = 0.000 < α = 0.05); and (3) there is no significant interaction between teaching methods and learning media in influencing chemistry learning outcomes (p = 0.317 > α = 0.05). This shows that teaching methods and learning media have an independent influence on chemistry learning outcomes